2021
DOI: 10.1051/matecconf/202134100032
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical background for the creation of wear-resistant coatings at the carbo-vibro-arc hardening

Abstract: The paper presents the results of theoretical studies that allow predicting the formation of wear-resistant coatings on the working surfaces of machine parts by the method of carbo-vibro-arc hardening (CVAH). Analytical regularities of electric field intensity formation by oscillating carbon electrode during carbo-vibro-arc hardening (CVAH) have been established; the maximum layer thickness of multicomponent paste, 2.1...2.5 mm, which ensures stable electric arc combustion during CVAH, has been theoretically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Fodder production is certain to be a fundamental branch of agriculture. [40][41][42][43][44][45]. In feeding Jerusalem artichoke tubers and herbage to animals, it was found that these types of feed were highly attractive for all kinds of animals and preferred over other types of forage [1, [46][47][48][49][50].…”
Section: Value Of Jerusalem Artichoke As a Forage Cropmentioning
confidence: 99%
“…Fodder production is certain to be a fundamental branch of agriculture. [40][41][42][43][44][45]. In feeding Jerusalem artichoke tubers and herbage to animals, it was found that these types of feed were highly attractive for all kinds of animals and preferred over other types of forage [1, [46][47][48][49][50].…”
Section: Value Of Jerusalem Artichoke As a Forage Cropmentioning
confidence: 99%